ELABORATION OF PRIMER ON COMPLEMENTARY FOOD: A COMPILATION OF EXPERIENCES OF A GROUP OF MOTHERS IN CAUCAIA-CE - Soares Damasceno, Leandro; Paula Lima Ribeiro, Ana; Cunto de Vasconcelos, Annunziata; Meirivam Mendonça Pereira, Antonia; Raquel Ferreira de Carvalho, Teresa; Maria Maia de Melo, Letícia; Regina Silveira, Elaine; Gonçalves Nascimento Costa Cordeiro, Cintia; Janaina de Sousa, Ingreth; Alves de Menezes, Naitlha (Health and Society, 2024)
The inclusion of complementary feeding is an important and difficult step for the child and his / her caregivers. In this period, the development of self-control of food intake by the child depends on the food and the form that are offered. Thus, the objective of the study was to elaborate an educational booklet with healthy eating guidelines, based on the experiences of a group of mothers. A qualitative and quantitative research was carried out, with a cross - sectional design and a discourse analysis methodology. The population was 20 mothers who had children over 1 year, since they have already undergone the introduction of food. Data collection was performed through an individual interview, with the application of guiding questions. Breastfeeding extended to six months of age did not prove to be a prevalent practice among the interviewed mothers, since 45% offered food and teas before completing the 6 months. According to the results, we can see that breastfeeding and complementary feeding are not yet within the desired results of the Food Guide. However, these results are not related to lack of information, support and encouragement to breastfeeding and healthy eating, since most mothers reported receiving guidance on these subjects.